Antioxidant activity of different extracts from leaves of Pereskia bleo (Cactaceae) - Hassanbaglou, Behnaz; Abdul Hamid, Azizah; A. M., Roheeyati; Mohd Saleh, Norihan; Abdulamir, AhmadSahib; Khatib, Alfi; Sabu, MC (Academic Journals, 2012)
The present study was conducted to assess the antioxidant properties of ethanol, ethyl acetate, methanol and hexane extracts from leaves of Pereskia bleo using 2,2-diphenyl-1-picrylhydrazyl method (DPPH assay), ferric reducing antioxidant power (FRAP assay) and β-Carotene-Linoleic acid methods. Total phenolic compounds (TPC) and flavonoids of the leaves of P. bleo were measured using Folin-Ciocalteu and HPLC methods respectively. Results of the present study showed that Ethyl acetate extract of P. bleo leaf exhibited significantly (p < 0.05) higher antioxidant activity as measured using DPPH free radical (IC50), FRAP and β-carotene-linoleic assays than that of hexane extract, methanol extract and ethanol extract. Pereskia bleo leaf was also found to contain high amounts of bioactive compounds including total phenolic compounds (109.43 ±0.84 mg GAE/g), epicatechin (575± 0.04 mg/100g), quercetin (110.94 ±0.12 mg/100g), catechin (918 ± 0.01 mg/100 g) and myricetin (9.49±0.55 mg/100g) while the concentrations of α- tocopherol, β-carotene and lycopene were found to be higher (69±0.25, 51.97±1.18 mg/100 g, 92.46±0.41 μg/g), respectively.